(untitled) (Perner’s Contacts, 2017)
The paper is focused on hazardous materials transportation by road and investigates risk factors influencing risk associated with such transportation. Statistical data on dangerous goods transportation in the Czech Republic are used in order to compute transportation patterns and identify time distribution of accidents. Numerical approach to determine a risk of time in hazmat transportation is presented. Measures reducing risk of hazardous material transportation are proposed in this paper.